2023
DOI: 10.1038/s41398-023-02309-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple measurement analysis of resting-state fMRI for ADHD classification in adolescent brain from the ABCD study

Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in school-aged children. Its accurate diagnosis looks after patients’ interests well with effective treatment, which is important to them and their family. Resting-state functional magnetic resonance imaging (rsfMRI) has been widely used to characterize the abnormal brain function by computing the voxel-wise measures and Pearson’s correlation (PC)-based functional connectivity (FC) for ADHD diagnosis. However, explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Brain imaging techniques have been largely applied to the study of ADHD, where magnetic resonance imaging studies have revealed smaller global brain volumes in ADHD subjects, particularly children ( 48 , 49 ). Moreover, neuroimaging literature on ADHD is inconclusive with small effect sizes unable to inform clinical practice ( 50 ) as these differences are not specific to ADHD, where neuroimaging studies on other developmental disorders, such as autism, have also shown similar differences in brain volume ( 51 , 52 ) when compared to controls.…”
Section: Executive Dysfunction Theorymentioning
confidence: 99%
“…Brain imaging techniques have been largely applied to the study of ADHD, where magnetic resonance imaging studies have revealed smaller global brain volumes in ADHD subjects, particularly children ( 48 , 49 ). Moreover, neuroimaging literature on ADHD is inconclusive with small effect sizes unable to inform clinical practice ( 50 ) as these differences are not specific to ADHD, where neuroimaging studies on other developmental disorders, such as autism, have also shown similar differences in brain volume ( 51 , 52 ) when compared to controls.…”
Section: Executive Dysfunction Theorymentioning
confidence: 99%
“…To analyze the nonparametric correlations of multiple input variables, we used a random forest-based feature selection Boruta algorithm 63 . Its robustness and effectiveness in selecting relevant features in high dimensional, intercorrelated biomedical data (e.g., MRI) has been validated 63 and consistently applied in genetics and neuroscience research [64][65][66] . The variables significantly correlated with delay discounting (p-Bonferroni<0.05) were GPS of cognitive performance, IQ, and education attainment; morphometric features (e.g., surface area, volume) in the limbic system (temporal pole, parahippocampal gyrus, caudate nucleus, rostral anterior cingulate, isthmus cingulate), inferior frontal gyrus (pars opercularis), and fusiform gyrus; mean beta activations of rewards/losses versus neutral feedback in the subcortical areas (thalamus proper, ventral diencephalon), precentral gyrus, supramarginal gyrus, temporal lobe (transverse temporal gyrus, superior temporal gyrus), and insula (Supplementary Table 4).…”
Section: Delay Discountingmentioning
confidence: 99%
“…These studies motivate the need to discover ADHD biotypes with homogeneous structural or functional signatures. To date, eight studies have identified ADHD biotypes using different neuroimaging measures, such as structural morphology (16,17), functional connectivity (18)(19)(20)(21), and combinations of both features (22,23). These results have already begun to provide insights into the neurophysiological heterogeneity of ADHD.…”
Section: Introductionmentioning
confidence: 99%